School health systems under strain: an example of COVID-19 experiences & burnout among school health staff in Pima County, Arizona - Amanda M. Wilson; Priyanka Ravi; Nicole T. Pargas; Lynn B. Gerald; Ashley A. Lowe (BMC, 2023)
Abstract Background School health staff lead and provide a variety of care for children in schools. As school districts have navigated the COVID-19 pandemic, school health staff have faced unprecedented challenges in protecting the health of students and school staff. Our objective was to qualitatively characterize these pandemic challenges and experiences of school health staff in Pima County, Arizona to identify gaps in school health staff support for improving future emergency preparedness. Methods We conducted two focus group discussions (FGDs) with 48 school health staff in Pima County, Arizona in two school districts using a discussion guide including ten open-ended questions. The FGDs were audio recorded and transcribed verbatim. We used the socioecological model (SEM) to organize the thematic analysis and generate codes and themes; data were analyzed using Atlas.ti software. Findings The pandemic has significantly challenged school health staff with new pandemic-related job tasks: managing isolation, vaccination, and developing/implementing new and evolving COVID-19 guidelines. School health staff also reported increased stress related to interactions with parents and school administration as well as frustrations with rapid changes to guidance from the health department and policy makers. A common issue was not having enough staff or resources to complete regular job responsibilities, such as providing care for students with non-COVID-19 related health issues. Conclusions Increased workload for school health staff resulted in physical burnout, mental distress, and disruption of core functions with long term implications for children's health. These focus groups highlight the need for improved emergency preparedness in schools during pandemics or infectious disease outbreaks. These include basic infrastructure changes (e.g., personnel support from health departments for tasks such as contact tracing to enable school nurses to continue core functions), and increased funding to allow for hazard pay and more school health personnel during emergency situations. In addition, basic school health infrastructure is lacking, and we should include a licensed school health nurse in every school.